SOME SOIL PROPERTIES OF THE GRABAG-PRINGSURAT PALEOCHANNEL (CENTRAL JAVA) INDICATING THE FATE OF PEDOGENESIS UNDER A SPECIFIC GEOMORPHOLOGICAL SITUATION - Grace Helena Amaranthois Kapisan; Arif Ashari; Summayah Aimi Mohd Najib; Muhamad Ervin; Muhammad Asrori Indra Wardoyo; Bagas Syarifudin; Kamila Nur Fitriana; Raisya Arzety Olivia; Greace Nanda Putri Salma; Az-Zahra Arhdhana Reswari; Kinanthi Purbaning Yuangwidi; Bagus Tegar Sakti Prakosa (JURNAL GEOGRAFI Geografi dan Pengajarannya, 2026)
Along with landform development, the soil on a landform also undergoes development characterized by various changes in physical and chemical characteristics. In this paper, we present the results of an investigating in to the physical and chemical characteristics of the soil in the paleochannel. The study was conducted in the Grabag-Pringsurat area where there are paleochannels with Pleistocene-aged materials. The study implemented the synthetic soil survey method. Nine paleochannels were selected as samples for observation. The data was then analyzed descriptively. There are two significant findings in this study. First, the physical properties of the soil are characterized by a dark color, fine-loamy texture, structural arrangement with strong aggregates, and strong consistency. In contrast, the chemical properties are characterized by acidic soil reactions. Second, soil properties are more developed in paleochannels filled with older materials. Overall, this study provides alternative information that reinforces the concept of soil development as an integral part of landform development. Keywords: Soil, Soil Properties, Soil-Geomorphology, Landform, Paleochannel